2013
DOI: 10.12674/ptk.2013.20.2.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inflatable Standing Surface With Different Levels of Air Pressure on Leg Muscle Activity

Abstract: 1)The purpose of this study was to determine the effect of the changes that occur in the leg muscle activity of unstable surface with different levels of air pressures. Three groups of college students have been placed randomly on unstable surfaces with different air pressures at group 1.0 psi (n1=36), group 1.4 psi (n2=40), and group 1.8 psi (n3=40). Using surface electromyography, the recruitment of the tibialis anterior, peroneus longus, and the gastrocnemius was measured. Maximal voluntary isometric contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In this study, subjects with exercises on sands were found to have more improvement in balancing capability than those with exercises on normal hard ground. Exercises on unstable bearing surface like that of sands might be effective ways to strengthen muscles and train proprioceptive sensation [38]. The results of this study showed that walking on sand has the potential to reduce the resultant inflammatory markers relative to matched exercise intensities on a hard surface.…”
Section: Discussionmentioning
confidence: 73%
“…In this study, subjects with exercises on sands were found to have more improvement in balancing capability than those with exercises on normal hard ground. Exercises on unstable bearing surface like that of sands might be effective ways to strengthen muscles and train proprioceptive sensation [38]. The results of this study showed that walking on sand has the potential to reduce the resultant inflammatory markers relative to matched exercise intensities on a hard surface.…”
Section: Discussionmentioning
confidence: 73%
“…A previous study emphasized intervention measures using an unstable support, showing that exercises performed on an unstable support were more effective in improving proprioception than those on a stable support even during weight-shift training; and were effective for promoting sensory-motor feedback by facilitating balance training and the motor control strategy around the ankle, and for enhancing the muscle contraction strategy that strengthens weakened muscles 2 ) . Previous studies reported the effects of unstable supports on lower-extremity muscle activity according to differences in air pressure 3 ) , the effects of exercises using unstable supports on gait and balance ability 4 ) , and the effects of variable bridging exercises on trunk and lower-extremity muscle activity 5 ) . However, most of those studies were limited to the effects of unstable supports on flat ground, and there are comparatively few studies on the effects of unstable supports and changes in inclined board angle.…”
Section: Introductionmentioning
confidence: 99%
“…4) 안정 지지면과 비교 하여 불안정 지지면에서의 운동은 체중이동 훈련 시에도 고유 수용성감각 향상에 더 효과적이며, 균형훈련과 발목 주변의 운동조절 전략을 활성화시켜 감각운동 되먹임을 증진시키는 효과와 약화된 근육을 강화시키기 위해 효과적이라는 연구결 과로 불안정 지지면에서의 중재를 강조하였다. 5) 닫힌 사슬운동은 팔다리의 먼쪽부분이 고정되어 있는 상태 에서 몸쪽부분과 먼쪽부분에서 저항을 동시에 적용할 때 일어 나는 운동이며, 6) 열린 사슬운동은 사지의 먼쪽부분이 자유롭 게 움직이고 몸쪽부분에서는 고정된 상태에서 운동을 시행하 는 방법을 말한다. 7) 대항근이 서로 편심성(eccentric)으로 작용하여 손상된 관 절의 안정성에 많은 영향을 주므로 주요 근력강화프로그램 중 하나이고 근력강화 훈련이 균형능력 증진에 더 효과적이라 보…”
Section: 서 론unclassified